An Investigation into the predictors of brand preference towards cement brands available on the South African Market: A Consumer’s Perspective - Goitumetswe Pitso; Neo Ligaraba; Tinashe Chuchu (Profesional Muda Cendekia Publishing, 2023)
The present study examines the antecedents and outcomes of brand preference in the South African Cement Industry. Due to the unavailability of a sampling frame, non-probability sampling, a form of convenience sampling was adopted to determine suitable respondents. A self-administered questionnaire was utilised to obtain 260 valid responses from individuals identifying as customers of the South African cement industry. To analyse the data, descriptive statistics and hypotheses testing was conducted through SPSS28 and AMOS 28 respectively. The findings of the study revealed that perceived quality, brand image, price and the influence of others positively impact brand preference. Brand preference positively influences word-of-mouth and purchase intentions and packaging do not play significant roles as antecedents of brand preference in the cement industry. It is imperative to allocate most of the organisation’s resources towards increasing brand preference as it has the most impact on purchase intention. This study explored the choice of cement brand from a business-to-business point of view and from a retail to consumer point of view. This is first study to investigate brand preference in the South African Cement Industry.